2012
DOI: 10.1124/dmd.112.045682
|View full text |Cite
|
Sign up to set email alerts
|

Microdialysis Evaluation of Clozapine and N-Desmethylclozapine Pharmacokinetics in Rat Brain

Abstract: ABSTRACT:A significant barrier to realization of the full potential of clozapine as a therapeutic agent in the treatment of schizophrenia is the substantial interpatient variability that exists along the therapeutic continuum of no response-efficacious response-adverse response. Genetic polymorphisms that manifest as highly variable pharmacodynamic and pharmacokinetic measures are its expected causes. To support investigations that seek to understand these causes, the plasma and central nervous system pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
(37 reference statements)
1
22
0
Order By: Relevance
“…In rats, 10 mg/kg clozapine (s.c.) leads to a peak unbound plasma level from intracranial microdialysis sampling of ∼0.07 µ m , and a delayed peak level of 0.008 µ m N -Des (Cremers et al, 2012). At this dose, clozapine has been shown to reduce amphetamine hyperlocomotion (Natesan et al, 2007) and reduces the ASR in rats (Conti et al, 2005; Feifel et al, 2011), just as we observed after CNO administration.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, 10 mg/kg clozapine (s.c.) leads to a peak unbound plasma level from intracranial microdialysis sampling of ∼0.07 µ m , and a delayed peak level of 0.008 µ m N -Des (Cremers et al, 2012). At this dose, clozapine has been shown to reduce amphetamine hyperlocomotion (Natesan et al, 2007) and reduces the ASR in rats (Conti et al, 2005; Feifel et al, 2011), just as we observed after CNO administration.…”
Section: Discussionmentioning
confidence: 99%
“…To get the maximal therapeutic window of drugs, clozapine at 100 mg/kg was chosen to investigate the drug-drug interaction effects of rhein on the PK and PD of clozapine in rat brain. Although studies of clozapine and norclozapine PK in the rat mPFC by in vivo microdialysis and HPLC-MS/MS have been reported (Cremers et al, 2012;Li et al, 2014), there are no studies of drug-drug interactions of rhein on clozapine PK in the rat mPFC. Thus, the PK of clozapine and norclozapine in rat mPFC was conducted by in vivo microdialysis in conscious rats.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ionpair high-performance liquid chromatography-electrochemical detection (HPLC-ECD) is of great interest for the determination of monoamine neurotransmitters [i.e., norepinephrine; epinephrine; 3,4-dihydroxyphenylacetic acid (DOPAC); DA; 5-hydroxyindole-3-acetic acid (5-HIAA); homovanillic acid (HVA); 5-HT; and 3-methoxytyramine hydrochloride] in microdialysis samples (Bicker et al, 2013). Moreover, ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) has been used to quantify the concentrations of drug and its metabolites in microdialysate (Cremers et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The 6-fold higher unbound brain ECF concentrations seen for oxycodone compared to morphine were proposed to explain this phenomenon, and modelling of these concentrations supported this theory, as demonstrated by a higher uptake clearance than efflux clearance across the BBB for oxycodone, while the reverse result was obtained for morphine (43). Another example of application-based modelling for CNS drugs was presented by Cremers et al (44) for the anti-psychotic drug clozapine and its active human metabolite Ndesmethylclozapine. The highly variable response to clozapine treatment in patients with schizophrenia is thought to be due to inter-patient variability in ECF concentrations, for the same plasma concentrations.…”
Section: Compartmental Pk Modelsmentioning
confidence: 96%